2010
DOI: 10.1088/0004-637x/716/2/1438
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Magnetic Fields in the Antennae Galaxies

Abstract: We present self-consistent high-resolution simulations of NGC4038/4039 (the "Antennae galaxies") including star formation, supernova feedback and magnetic fields performed with the N -body/SPH code Gadget, in which magnetohydrodynamics are followed with the SPH method. We vary the initial magnetic field in the progenitor disks from 10 −9 to 10 −4 G. At the time of the best match with the central region of the Antennae system the magnetic field has been amplified by compression and shear flows to an equilibrium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
79
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(99 citation statements)
references
References 98 publications
(125 reference statements)
20
79
0
Order By: Relevance
“…We have performed simulations of three colliding galaxies to proof the saturation and equipartition phenomena seen in Kotarba et al, 2010a on the basis of a more general setup (Kotarba et al, 2010b). In these simulations, the magnetic field saturates at a value of about 1 G -which is again consistent with observations -, independent of the initial value.…”
Section: Simulationssupporting
confidence: 69%
See 1 more Smart Citation
“…We have performed simulations of three colliding galaxies to proof the saturation and equipartition phenomena seen in Kotarba et al, 2010a on the basis of a more general setup (Kotarba et al, 2010b). In these simulations, the magnetic field saturates at a value of about 1 G -which is again consistent with observations -, independent of the initial value.…”
Section: Simulationssupporting
confidence: 69%
“…A perfect example of the strong coupling of gas and magnetic fields is the interacting system NGC4038/4039 (the "Antennae galaxies"). We have simulated this system including magnetic fields for the first time (Kotarba et al, 2010a). The simulations demonstrated that even an initial magnetic field as small as 10 −9 G is efficiently amplified during the interaction of two equal-mass spiral galaxies.…”
Section: Simulationsmentioning
confidence: 99%
“…The average total magnetic field is stronger than that in normal spirals, but the mean degree of polarization is unusually low, implying that the fields are tangled. The Antennae galaxies have been modelled by Kotarba et al (2010), who could reproduce the main features observed in the radio image.…”
Section: Beyond Spirals: Interacting Galaxiesmentioning
confidence: 99%
“…Since gas and magnetic fields are tightly coupled, the magnetic fields trace the gas motion and will be strengthened by shocks and gas inflow. A perfect example for the strong coupling of gas and magnetic fields is the interacting system NGC 4038/4039 (the ‘Antennae galaxies’) which has been recently simulated (Karl et al 2010) by Kotarba et al (2010) including magnetic fields. It was shown that even an initial magnetic field as small as 10 −9 G grows significantly during the interaction of two equal‐mass spiral galaxies.…”
Section: Introductionmentioning
confidence: 99%